2015
DOI: 10.1016/j.celrep.2015.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Derived Cytosolic DNA Mediates Type I Interferon-Dependent Rejection of B Cell Lymphoma Cells

Abstract: The DNA damage response (DDR) induces the expression of type I interferons (IFNs), but the underlying mechanisms are poorly understood. Here, we show the presence of cytosolic DNA in different mouse and human tumor cells. Treatment of cells with genotoxic agents increased the levels of cytosolic DNA in a DDR-dependent manner. Cloning of cytosolic DNA molecules from mouse lymphoma cells suggests that cytosolic DNA is derived from unique genomic loci and has the potential to form non-B DNA structures, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 38 publications
10
133
0
Order By: Relevance
“…In pilot experiments, we observed that the treatment of mammalian cells with X-irradiation led to an accumulation of ssDNA in the cytosol, an observation consistent with several other studies that report that genomic stress is associated with the accumulation of ssDNA in the cytosol (Shen et al 2015;Ho et al 2016). To further investigate whether DNA damage processing can lead to DNA fragments escaping the nucleus, a range of breast cancer cell lines (MCF7, BT474, MDA-MB-231, HCC1806, and T47D) was treated with IR (X rays) or DNA-damaging chemotherapeutics (mitomycin C or cisplatin) that induce distinct forms of DNA damage.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In pilot experiments, we observed that the treatment of mammalian cells with X-irradiation led to an accumulation of ssDNA in the cytosol, an observation consistent with several other studies that report that genomic stress is associated with the accumulation of ssDNA in the cytosol (Shen et al 2015;Ho et al 2016). To further investigate whether DNA damage processing can lead to DNA fragments escaping the nucleus, a range of breast cancer cell lines (MCF7, BT474, MDA-MB-231, HCC1806, and T47D) was treated with IR (X rays) or DNA-damaging chemotherapeutics (mitomycin C or cisplatin) that induce distinct forms of DNA damage.…”
Section: Resultssupporting
confidence: 76%
“…Indeed, ATM deficiency and the resulting unrepaired DNA damage result in the accumulation of cytosolic DNA and STING-dependent IFN induction (Hartlova et al 2015). Similarly, treatment of mouse B-cell lymphoma cells and human lung carcinoma cells with a replication inhibitor showed induction of cytosolic DNA (Shen et al 2015). Further findings suggest the possibility that release of MUS81-induced cytosolic DNA by prostate cancer cells contributes to STING activation (Ho et al 2016), where such fragments might be a by-product of MUS81-mediated replication fork processing in these cells (Ciccia et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…p53 pathway was upregulated in cDKO HSCs ( Figure 4E) and the IFN genes were dramatically enriched in cDKO HSCs ( Accumulation of unrepaired DNA lesions has recently been shown to activate the type I IFN pathway and inhibit stem cell function through the release of ssDNA into the cytoplasm. [44][45][46] Consistent with this, cDKO HSPCs and BM sections showed the presence of ssDNA in the cytoplasm ( Figure 5A; supplemental Figure 5A), as with that of positive control cells (Ctrl HSPCs treated with aphidicolin or lipopolysaccharide) (supplemental Figure 5B). Functionally, IFN signaling is reported to force HSCs to exit quiescence and enter the cell cycle, leaving them vulnerable to DNA damage.…”
Section: Cdko Causes Loss Of Hematopoietic Stem and Progenitor Cells supporting
confidence: 61%
“…This phenotype can be rescued by supplementation with nucleosides or by knockdown of p53, suggesting that replication-stressassociated DNA damage and p53 induction are major effectors of cell death in cDKO cells. We propose that ssDNA generated from unrepaired DNA damage induces cell-intrinsic activation of the interferon pathway, [44][45][46] which perturbs HSC quiescence, primes HSPCs for p53-mediated apoptotic cell death, and ultimately contributes to HSPC depletion ( Figure 7D). 29,48,54 These findings indicate that Ssb1 and Ssb2 coordinately protect organs from endogenous replication stress during normal physiology and are essential genome guardians for homeostasis of BM stem and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe a simple and quick (<4 hr) protocol to establish fibroblast cultures from ears and tails of mice 11 . The protocol requires minimal mouse experience to harvest the tissues (in contrast to other protocols 12,13 ) and can be used to establish cultures from ears stored in medium at RT for up to 10 days.…”
Section: Introductionmentioning
confidence: 99%